"Are we nearly there yet?" Lessons for integrated sustainability assessment from EU environmental policy-making. (15th May 2008) - Turnpenny, John
Increased interest in sustainable development, and in policy assessment as a means to achieve that, have yielded little evidence of sustainable development principles in policy assessment. This paper presents a study at a more strategic level of policy-making: the European Union (EU)'s environmental Thematic Strategies (TSs). Elements of Integrated Sustainability Assessment (ISA), such as consultation, were often strong, and quantitative analysis was integrated into policy development. But the primary aim of EU policy of pursuing economic growth and de regulation limits the scope and effectiveness of sustainability assessment. This paper concludes by drawing on literature on evidence in policy-making to suggest lessons for ISA.